Tinjauan Aspek Motif dan Bentuk pada Kriya Tas Batik Sumatera Utara di Sanggar Seni Pendopo - Muhammad Rizky; Misgiya Misgiya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article or writing aims to find out the motifs and shapes applied to the North Sumatran batik bag craft produced by the Pendopo art studio, by conducting a review of the bag product. The review is carried out so that later it will be more flexible in conducting an analysis of the product to be studied. This study uses a qualitative descriptive method with a population of 10 batik craft products. The problem is focused on motifs and forms. In order to approach this problem, a total sampling theory reference is used to collect data in the field starting from April to June, and begins through the process of observation, documentation interviews, data processing, data analysis, to drafting the thesis. The data were collected through direct observation and analyzed by qualitative descriptive method. This study concludes that several additional elements in the developed motifs are in the form of circle points and lines. However there is one pattern found in the form of a motif resembling a jasmine flower.